Vertical Sand Flux Density and Grain-Size Distributions for Wind-Blown Sand Over a Gobi Surface in Milan, Southern Xinjiang, China - Tan, Lihai; Zhang, Kai; Wang, Hongtao; An, Zhishan; Wang, Tao (Frontiers in Environmental Science, 2022)
Vertical sand flux density and grain-size distributions of wind-blown sand over gobi are an essential way for examining the complex grain-bed collisions over gobi surfaces and then understanding aeolian saltation dynamics. However, compared with sand surfaces, relatively few studies have reported regarding how sand flux density and grain size vary with elevation for wind-blown sand over gobi, especially in a field scale. Here, vertical sand flux density and grain-size distributions for wind-blown sand over a typical gobi surface during three transport events were revealed. The results show that the sand flux density exponentially decreased with elevation, which is different from the previous wind tunnel studies, and 99% of the sand transport amount was concentrated in the near-surface layer of 0.6 m. The mean grain size (Dm) first increased with elevation until an inflection in grain-size trends occurred at 0.175 m or 0.285 m above the ground, and then Dm decreased with height, which is significantly different from the vertical grain-size profile patterns of sand surfaces. The grain-bed collision process of medium sand over the gobi surface caused the increase of the mean grain size with height. Sorting was dominated by moderately sorted, skewness by symmetrical or fine skewed, and kurtosis by mesokurtic. The results of this study are significant for future numerical modeling studies of aeolian saltation over rough surfaces on Earth and even on Mars.